2016
DOI: 10.1038/tp.2016.154
|View full text |Cite
|
Sign up to set email alerts
|

Molecular signatures associated with cognitive deficits in schizophrenia: a study of biopsied olfactory neural epithelium

Abstract: Cognitive impairment is a key feature of schizophrenia (SZ) and determines functional outcome. Nonetheless, molecular signatures in neuronal tissues that associate with deficits are not well understood. We conducted nasal biopsy to obtain olfactory epithelium from patients with SZ and control subjects. The neural layers from the biopsied epithelium were enriched by laser-captured microdissection. We then performed an unbiased microarray expression study and implemented a systematic neuropsychological assessmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 61 publications
2
29
0
Order By: Relevance
“…The olfactory neural epithelium has received increasing interest as a surrogate tissue to study brain disorders . Multiple studies have shown that the molecular profiles of brain cells are much closer to those of the olfactory epithelium, compared to those of blood cells . The olfactory epithelium harbors olfactory receptor neurons at different stages of development, and offers a unique resource for investigating both state and trait biomarkers for psychiatric disorders .…”
Section: Patient Neuronal Sample Collectionmentioning
confidence: 99%
See 3 more Smart Citations
“…The olfactory neural epithelium has received increasing interest as a surrogate tissue to study brain disorders . Multiple studies have shown that the molecular profiles of brain cells are much closer to those of the olfactory epithelium, compared to those of blood cells . The olfactory epithelium harbors olfactory receptor neurons at different stages of development, and offers a unique resource for investigating both state and trait biomarkers for psychiatric disorders .…”
Section: Patient Neuronal Sample Collectionmentioning
confidence: 99%
“…One significant limitation to the use of the olfactory epithelium is the lack of purity of nasal biopsies, as the tissue contains a number of non‐neuronal cells. To enrich neuronal cell populations, endoscope‐guided nasal punch is combined with laser‐capture microdissection (LCM) to dissect the neuronal tissue . Nevertheless, glia‐like sustentacular (non‐neuronal) cells cannot be excluded with this method.…”
Section: Patient Neuronal Sample Collectionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, by using neural layers from biopsied OE enriched by LCM, the SMAD pathway was found to be downregulated and potentially associated with cognitive deficits in SZ [16]. A significant decrease in the density of p75-NGFR- positive basal cells in SZ OE nasal biopsies was also observed, suggesting dysregulation in the development of ORNs [11].…”
Section: Findings From Oe-derived Tissue/cell Models Obtained From Szmentioning
confidence: 99%